In Situ Photosynthesis of an MAPbI3/CoP Hybrid Heterojunction for Efficient Photocatalytic Hydrogen Evolution. (6th July 2020) - Cai, Cheng; Teng, Yuan; Wu, Jian‐Hao; Li, Jun‐Yan; Chen, Hong‐Yan; Chen, Jing‐Hua; Kuang, Dai‐Bin
Abstract: Halide perovskite like methylammonium lead iodide perovskite (MAPbI3 ) with its prominent optoelectronic properties has triggered substantial concerns in photocatalytic H2 evolution. In this work, to attain preferable photocatalytic performance, a MAPbI3 /cobalt phosphide (CoP) hybrid heterojunction is constructed by a facile in situ photosynthesis approach. Systematic investigations reveal that the CoP nanoparticle can work as co‐catalyst to not only extract photogenerated electrons effectively from MAPbI3 to improve the photoinduced charge separation, but also facilitate the interfacial catalytic reaction. As a result, the as‐achieved MAPbI3 /CoP hybrid displays a superior H2 evolution rate of 785.9 µmol h −1 g −1 in hydroiodic acid solution within 3 h, which is ≈8.0 times higher than that of pristine MAPbI3 . Furthermore, the H2 evolution rate of MAPbI3 /CoP hybrid can reach 2087.5 µmol h −1 g −1 when the photocatalytic reaction time reaches 27 h. This study employs a facile in situ photosynthesis strategy to deposit the metal phosphide co‐catalyst on halide perovskite nanocrystals to conduct photocatalytic H2 evolution reaction, which may stimulate the intensive investigation of perovskite/co‐catalyst hybrid systems for future photocatalytic applications. Abstract : A methylammonium lead iodide perovskite (MAPbI3 )/ cobalt phosphide (CoP) hybrid heterojunction for photocatalytic H2 evolution is synthesized by a facile in situ photosynthesis approach. In this hybrid, CoP nanoparticles can work as a co‐catalyst to not only extract photogenerated electrons effectively from MAPbI3 to improve the photoinduced charge separation, but also facilitate the interfacial catalytic reaction, which further contributes to an enhanced H2 evolution activity.